2022
DOI: 10.1371/journal.pone.0266649
|View full text |Cite
|
Sign up to set email alerts
|

The role of telepathology in diagnosis of pre-malignant and malignant cervical lesions: Implementation at a tertiary hospital in Northern Tanzania

Abstract: Introduction Adequate and timely access to pathology services is a key to scale up cancer control, however, there is an extremely shortage of pathologists in Tanzania. Telepathology (scanned images microscopy) has the potential to increase access to pathology services and it is increasingly being employed for primary diagnosis and consultation services. However, the experience with the use of telepathology in Tanzania is limited. We aimed to investigate the feasibility of using scanned images for primary diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Tanzania, Cameroon, Pakistan) where there is a critical shortage of pathology services necessary for clinical care. 16 21 Clinical applications addressed not only the benefit of digitizing slides in general surgical pathology, but also niche areas of practice such as telepathology for seeking second opinions (teleconsultation) in organ transplantation. 22 , 23 The critical need to provide remote care and education virtually in pathology during the COVID-19 pandemic acted as a catalyst for the adoption of DP around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Tanzania, Cameroon, Pakistan) where there is a critical shortage of pathology services necessary for clinical care. 16 21 Clinical applications addressed not only the benefit of digitizing slides in general surgical pathology, but also niche areas of practice such as telepathology for seeking second opinions (teleconsultation) in organ transplantation. 22 , 23 The critical need to provide remote care and education virtually in pathology during the COVID-19 pandemic acted as a catalyst for the adoption of DP around the world.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 25 studies concluded equivalent performance of digital pathology in comparison with light microscopy for routine diagnosis of medical conditions ( 33 ). Digital image analysis is especially important in Africa and other areas of the world where well-trained pathologists are scarce ( 34 , 35 ). Slide scanners are more and more available in core facilities also in Africa, have similar energy requirements as microscopes, and scanning can be performed by any laboratory technician after a short training session.…”
Section: Discussionmentioning
confidence: 99%
“…These artifacts may occur during surgical removal, fixation, tissue processing, embedding and microtomy, staining, and mounting. 24 , 25 , 26 Therefore, training in the best practice of tissue processing and quality control is critical for successfully adopting and implementing digital pathology.…”
Section: Discussionmentioning
confidence: 99%